1952
DOI: 10.1021/jo01135a013
|View full text |Cite
|
Sign up to set email alerts
|

An ANTIMALARIAL ALKALOID FROM HYDRANGEA. XII. SYNTHESIS OF 3-[Β-Keto-Γ-(3-Hydroxy-2-Piperidyl) PROPYL]-4-QUINAZOLONE, THE ALKALOID

Abstract: H(1), 3-[/3-keto-ysynthesized via 3-methoxypiperidine-2-acetic acid and found to be the dl-form of the alkaloid.1•3The key type of intermediate necessary for the synthesis of a molecule such as I would be the 0, N-derivatives of 2-hydroxy-5-aminovaleric acid. Two different blocking groups on the hydroxyl were investigated, O-methyl and O-phenyl, and three blocking groups on the nitrogen: phthalyl, carbobenzoxy, and carbethoxy.Ethyl phenoxymalonate (V), prepared by chlorination of ethyl malonate and treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1953
1953
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Methylation of the dry disodium salt of l-benzoyl-3-hydroxypiperidine-2acetic acid (XXIX) to the methyl ether (XXXII) with methyl iodide proceeded in 43% yield and 18% of the lactone (XXX) was recovered by treatment of the mixture with acetic anhydride so that the bicarbonate-soluble methoxy acid (XXXII) could be separated from the bicarbonate-soluble hydroxy acid (XXIX) by conversion of the latter to the bicarbonate-insoluble lactone (XXX). Hydrochloric acid removal of the benzoyl group of XXXII, followed by carbethoxylation gave the oily l-carbethoxy-3-methoxypiperidine-2-acetic acid (XXXI), an intermediate in the first synthesis of the ¿¿-alkaloid (7). The side chain was lengthened to -bromoacetonyl, then condensed with sodio-4-quinazolone to the crystalline carbethoxy quinazolone (XXXIV), identical with that obtained in the first synthesis of the ¿¿-alkaloid (7).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Methylation of the dry disodium salt of l-benzoyl-3-hydroxypiperidine-2acetic acid (XXIX) to the methyl ether (XXXII) with methyl iodide proceeded in 43% yield and 18% of the lactone (XXX) was recovered by treatment of the mixture with acetic anhydride so that the bicarbonate-soluble methoxy acid (XXXII) could be separated from the bicarbonate-soluble hydroxy acid (XXIX) by conversion of the latter to the bicarbonate-insoluble lactone (XXX). Hydrochloric acid removal of the benzoyl group of XXXII, followed by carbethoxylation gave the oily l-carbethoxy-3-methoxypiperidine-2-acetic acid (XXXI), an intermediate in the first synthesis of the ¿¿-alkaloid (7). The side chain was lengthened to -bromoacetonyl, then condensed with sodio-4-quinazolone to the crystalline carbethoxy quinazolone (XXXIV), identical with that obtained in the first synthesis of the ¿¿-alkaloid (7).…”
mentioning
confidence: 68%
“…Hydrochloric acid removal of the benzoyl group of XXXII, followed by carbethoxylation gave the oily l-carbethoxy-3-methoxypiperidine-2-acetic acid (XXXI), an intermediate in the first synthesis of the ¿¿-alkaloid (7). The side chain was lengthened to -bromoacetonyl, then condensed with sodio-4-quinazolone to the crystalline carbethoxy quinazolone (XXXIV), identical with that obtained in the first synthesis of the ¿¿-alkaloid (7). The synthesis is completed by a twostage hydrolysis to the ¿¿-alkaloid (XXXVI).…”
mentioning
confidence: 99%
“…Further studies suggested that it must be the diastereoisomers of febrifugine that posses the antimalarial properties. Baker and co-workers [25] studied the antimalarial activities of synthesized samples of dl-febrifugine and found only one-half activity than the naturally occurring compound. Further, they discovered that it was actually the isofebrifugine that possessed the antimalarial properties, but was highly toxic in isolation to the other compounds found in the naturally occurring alkaloid [26].…”
Section: Naturally Occurring Quinazoline-based Compoundsmentioning
confidence: 99%
“…The preparation of piperidine analogues was the most expensive part, and deemed to be the real difficulty to produce halofuginone as well. So far, a lot of methods have been reported: The method illustrated in Scheme 3 was originally developed by Baker’s team [ 18 , 22 , 23 , 24 , 25 , 26 ]. Afterwards, the method was optimized a bit by Barringer et al, via changing reagents and catalyst, which successfully improved the yield by reducing the number of steps but without lowering the cost.…”
Section: Introductionmentioning
confidence: 99%